The Clinical Features Of Malaria In Pregnancy - Dafallah, Saad El Naim (Gezira Journal of Health Sciences, 2004)
Malaria is a global health problem affecting all age groups. Pregnant ladies are at high risk than the non pregnant ones. Malaria always presents with symptoms which enable us to have a high index of suspicion. Proper history and examination are important tools in excluding diseases simulating malaria. The common symptom of malaria is fever which usually occur during the erythorcytic cycle. The clinical manifestation of malaria range from completely a symptomatic infection to a fatal severe disease.